In Vitro Antibacterial Activity of Unconjugated and Conjugated Bile Salts on Staphylococcus aureus - Sannasiddappa, Thippeswamy H.; Lund, Peter A.; Clarke, Simon R. (Frontiers in Microbiology, 2017)
Bile salts are potent antimicrobial agents and are an important component of innate defences in the intestine, giving protection against invasive organisms. They play an important role in determining microbial ecology of the intestine and alterations in their levels can lead to increased colonization by pathogens. We have previously demonstrated survival of the opportunistic pathogen Staphylococcus aureus in the human colonic model. Thus investigating the interaction between S. aureus and bile salts is an important factor in understanding its ability to colonize in the host intestine. Harnessing bile salts may also give a new avenue to explore in the development of therapeutic strategies to control drug resistant bacteria. Despite this importance, the antibacterial activity of bile salts on S. aureus is poorly understood. In this study, we investigated the antibacterial effects of the major unconjugated and conjugated bile salts on S. aureus. Several concentration dependent antibacterial mechanisms were found. Unconjugated bile salts at their minimum inhibitory concentration (cholic and deoxycholic acid at 20 and 1 mM respectively) killed S. aureus, and this was associated with increased membrane disruption and leakage of cellular contents. Unconjugated bile salts (cholic and deoxycholic acid at 8 and 0.4 mM respectively) and conjugated bile salts (glycocholic and taurocholic acid at 20 mM) at their sub inhibitory concentrations were still able to inhibit growth through disruption of the proton motive force and increased membrane permeability. We also demonstrated that unconjugated bile salts possess more potent antibacterial action on S. aureus than conjugated bile salts.